Kajian Fenomenologis Teknologi Blockchain dalam Mencegah Fraud pada Pemerintah Kota Ternate - Septy Indra Santoso; Gregorius Jeandry (Al-Buhuts, 2025)
This study aims to understand the phenomenon of fraud within the bureaucracy of the Ternate City Government and to explore the potential implementation of blockchain technology as a preventive solution. Using a qualitative phenomenological approach, data were obtained through in-depth interviews with officials from the Regional Development Planning, Research, and Development Agency (Bappelitbangda) and the Regional Financial and Asset Management Agency (BPKAD). The findings reveal that fraud is not only triggered by individual behavior but also by structural weaknesses in the centralized information system (SIPD), which frequently experiences technical disruptions and data inconsistencies between government agencies (OPD). The Ternate City Government has developed backup systems such as SIMDA, EREMPAH, and SITORANG to support transparency and development monitoring. However, accountability remains a critical challenge. Blockchain technology, with its decentralized, transparent, immutable, and smart contract features, is seen as a strategic solution to strengthen the principles of good governance. Integrating blockchain with local systems could foster governance that is more transparent, accountable, participatory, and fraud-free.